The Influence of Brand Experience, Brand Trust, Brand Attachment on Customer Loyalty in an Islamic Business Perspective (Study on Generation Z Skintific Consumers In Bandar Lampung City) - Anggreini, Nava; Fasa, Muhammad Iqbal; Fachri, Adib (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine and analyze the effect of Brand Experience, Brand Trust, and Brand Attachment on Customer Loyalty in an Islamic Business Perspective, with a focus on Skintific Skincare users among generation Z in Bandar Lampung City. The methodology used is a survey with a questionnaire distributed to 97 respondents who are users of Skintific products. Data analysis was carried out using purposive sampling techniques, using the Nonprobability Sampling method and using the Lemeshow formula. The data analysis method using SEM PLS analysis is processed with the SmartPLS 4.0 application. The results showed that Brand Experience has a positive and significant effect on Customer Loyalty, Furthermore, Brand Attachment has a positive effect on Customer Loyalty. While brand Trust is proven to have no effect on customer loyalty. This research makes an important contribution to skincare companies in developing marketing strategies that are in accordance with Islamic business values, as well as helping companies build customer loyalty among generation Z.